LISTENING STRATEGY: A LINK BETWEEN GENDER AND STUDENT’S ACHIEVEMENT - Ika Hidayanti; Atik Umamah (Abjadia, 2019)
The recent study is investigating 1) the significant difference on the use of learning strategy by male and female students in listening, and 2) the correlation between the learning strategy use and two aspects of gender and listening proficiency. The questionnaire was directed to 140 university students to answer a-85 item of learning strategy. The t-test and correlation analysis were used to analyse the research problems. The first finding reveals that female students did not deploy the strategies significantly different from the male counterparts. The later result reports that there was no correlation between listening strategy and two factors ofgender and the students’ listening achievement.